IMPLEMENTASI MODEL PEMBELAJARAN GUIDED INQUIRY BERMUATAN ESD (EDUCATION FOR SUSTAINABLE DEVELOPMENT) UNTUK MEMBENTUK SUSTAINABILITY AWARENESS MURID - Wahyu Satriyo Wibowo; Erman Erman (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
The low level of sustainability awareness in Indonesia, as reflected in the 2024 Environmental Performance Index ranking, which places Indonesia at the bottom of the national ranking, demands systematic innovation in science learning. The main problem identified is the lack of explicit integration of sustainable development concepts into the secondary science curriculum, resulting in limited student sensitivity to ecological issues. This quantitative research, using a pre-experimental one-shot case study design, aims to measure the effectiveness of the guided inquiry learning model containing Education for Sustainable Development (ESD). The research stages were carried out through initial observations, designing a teaching module based on environmental pollution issues, and collecting data using a questionnaire from thirty-four seventh-grade students in East Java. The results showed that all learning sessions were implemented perfectly with a 100% success rate. Quantitative findings prove that students' sustainability awareness is in the high category in all three main aspects, with an average score of 3.07 for practical awareness, 3.24 for behavioral and attitudinal awareness, and 3.34 for emotional awareness. The main conclusion confirms that the integration of ESD within a guided inquiry framework significantly builds students' emotional sensitivity and ecological responsibility. This strategy effectively transforms theoretical material into a comprehensive environmental character to support the achievement of the global sustainable development agenda in a collaborative and real manner. ABSTRAK Rendahnya tingkat kesadaran keberlanjutan di Indonesia, sebagaimana tercermin dalam peringkat Environmental Performance Index 2024 yang menempatkan posisi nasional di urutan bawah, menuntut adanya inovasi sistematis dalam pembelajaran sains. Masalah utama yang diidentifikasi adalah belum terintegrasinya konsep pembangunan berkelanjutan secara eksplisit dalam kurikulum IPA di tingkat menengah, sehingga kepekaan siswa terhadap isu ekologis masih sangat terbatas. Penelitian kuantitatif dengan desain pre-experimental one-shot case study ini bertujuan mengukur efektivitas model pembelajaran guided inquiry bermuatan Education for Sustainable Development (ESD). Tahapan penelitian dilaksanakan melalui observasi awal, perancangan modul ajar berbasis isu pencemaran lingkungan, serta pengumpulan data menggunakan angket kepada tiga puluh empat murid kelas VII di Jawa Timur. Hasil penelitian menunjukkan bahwa seluruh sesi pembelajaran terlaksana secara sempurna dengan persentase keberhasilan seratus persen. Temuan kuantitatif membuktikan bahwa sustainability awareness murid berada pada kategori tinggi pada ketiga aspek utama, dengan skor rata-rata kesadaran praktik sebesar 3,07, kesadaran perilaku dan sikap sebesar 3,24, serta kesadaran emosional mencapai nilai tertinggi senilai 3,34. Simpulan utama menegaskan bahwa integrasi ESD dalam kerangka inkuiri terbimbing secara signifikan mampu membangun kepekaan emosional dan tanggung jawab ekologis siswa. Strategi ini efektif mentransformasi materi teoritis menjadi karakter peduli lingkungan yang komprehensif demi mendukung pencapaian agenda pembangunan berkelanjutan global secara kolaboratif dan nyata.